Antimicrobial activity of anacardium occidental leaves extract against selected gram positive and gram negative bacteria / Maryam Najihah Zainuddin - Zainuddin, Maryam Najihah (Faculty of Applied Sciences, 2017)
Anacardium occidentale is the tropical tree that can be used as traditional medicine for treating variety of disease. The present study was carried out to determine the phytochemical compound and anitimicrobial activity of methanol and hexane of the leaves of A. occidentale. In phytochemical screening, there were five tests done to detect the presence of saponins, tannins, phenols, flavanoids and alkaloids. The results obtained demonstrate that in A. occidentale leaves contained the same phytochemical compounds which were saponins, tannins, phenols and flavanoids. The antimicrobial activity of leaves extract was determined by the disc diffusion method. The results obtained revealed that A occidentale leaves was potential against gram positive and gram negative bacteria There were four concentration used (500 mg/ml, 250 mg/ml, 125 mg/ml and 65.5 mg/ml) for the leaves extract. The result showed that A. occidentale was effective against Bacillus subtilis, Klebsilla pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus. Concentration 500 mg/ml was the best concentration for A. occidentale leaves to inhibit the choosen bacteria. In conclusion, the leaves of A. occidentale was potential in inhibiting bacteria with significant value at p<0.05 in methanol extract.